Seasonality in Lipid Content of the Demosponges Halichondria panicea and H. bowerbanki at Two Study Sites in Temperate Danish Waters - Lüskow, Florian; Kløve-Mogensen, Kirstine; Tophøj, Jakob; Pedersen, Lars Haastrup; Riisgård, Hans Ulrik; Eriksen, Niels Thomas (Frontiers in Marine Science, 2019)
This study relates the lipid content of two marine filter-feeding demosponges, Halichondria panicea and H. bowerbanki to the seasonal availability of their suspended food, mainly free-living bacteria and phytoplankton at two study sites in Danish waters. The aim was to investigate if the lipid content of sponges is linked to food availability and season, and to what extend free-living bacteria are available in starvation periods where the phytoplankton biomass is low. The highest concentrations of bacteria were observed during summer when also chlorophyll a concentrations were high, and therefore bacteria and phytoplankton were available in similar ratio at all seasons. Bacterial cell carbon was estimated to contribute 2.9 and 4.6 % compared to phytoplankton cell carbon in the food at the two sites, respectively, and free-living bacteria were available only as a minor food source at all seasons. Highest lipid contents (29.5 % of sponge dry weight) were seen in H. panicea at the site with lowest food availability, while the lipid content of H. bowerbanki was 11.5 % of dry weight. No seasonal variations in lipid content as fraction of sponge dry weight were observed, and the lipid content was not affected by food availability or starvation. It remains unclear why the lipid-content levels at the two study sites were conspicuously different.